Competitiveness of sorghum production in northern Tamaulipas, Mexico - Alejandro Allende, Florencia; García Mata, Roberto; García Sánchez, Roberto Carlos; Mora Flores, José Saturnino; Sangerman Jarquín, Dora María (Revista Mexicana de Ciencias Agrícolas, 2020)
This research was carried out in northern Tamaulipas in the autumn-winter 2016-2017 cycle, based on information from 40 grain sorghum producers, where prices of the product, inputs and their technical production coefficients were obtained. With this information, private production costs were calculated. The objective of this work was to determine the competitiveness of the cultivation of sorghum grain by humidity-technology regime and producer size in northern Tamaulipas, by using the methodology of the policy analysis matrix in its private part. The results showed that the three technologies had a positive gain, a private profitability ratio, which was between 20.66% to 26.43% and a private cost ratio that stood between 0.4359 and 0.4642, indicating competitiveness, allowing the payment of internal factors, leaving a positive profit margin, provided that the payment for land rent is not considered. Intermediate consumption was between 62.78% and 71.53% of the value of production, which represents the purchase of inputs and services from other sectors of the economy. The added value varied from 28.47% to 37.22%, representing the minimum contribution in the generation of employment in this crop. In general, the results indicate that on average the three technologies used in production in northern Tamaulipas, without considering the income of the land were profitable and competitive, which allows to expect a future expansion of the production of this grain in the region study.
Keywords: competitiveness indicators; grain sorghum; private profitability; production costs